Growth-inhibitory effects of tris-(1,10-phenanthroline) iron (II) against Mycobacterium tuberculosis in vitro and in vivo - Solcia, Mariana Cristina [UNESP]; Campos, Débora Leite [UNESP]; Grecco, Júlia Araújo [UNESP]; Paiva Silva, Caio Sander [UNESP]; Bento da Silva, Patrícia [UNESP]; Cristiane da Silva, Isabel [UNESP]; Balduino da Silva, Ana Paula [UNESP]; Silva, Joás [UNESP]; Oda, Fernando Bombarda [UNESP]; Gonzaga dos Santos, André [UNESP]; Pavan, Fernando Rogério [UNESP] (Elsevier, 2021)
Mycobacterium tuberculosis is the major etiological agent for tuberculosis (TB), which is the leading cause of single pathogen infection-related deaths worldwide. The End TB Strategy of the World Health Organization aimed to decrease the incidence of TB by 20% between 2015 and 2020, which was not achieved. Here, the growth-inhibitory effects of tris-(1,10-phenanthroline) iron (II) complex ([Fe(phen)3]2+), a known commercially available cheap chemical substance, were examined. The best in vitro results showed great activity with MIC ranging from 0.77 to 3.06 μM against clinical strains and at low pH (mimicking the granuloma) with MIC of 0.21 μM. Preliminary safety analysis revealed that the complex did not exhibit cytotoxic activity against different cell lines or mutagenic activity in vitro. The complex was orally bioavailable after 2 h of administration in vivo. Additionally, the results of the acute toxicity test revealed that the complex did not exert toxic effects in female BALB/c mice. The mechanism of action was performed using D29 mycobacteriophages where the treatment with different concentrations of the complex inhibited viral protein synthesis, which indicated that the anti-TB mechanisms of the complex involve protein synthesis inhibition. These findings suggested that [Fe(phen)3]2+ is a potential novel therapeutic for TB.
Keywords: Drug repurposing; Efficacy; Mycobacterium tuberculosis; Safety; Tris-(1,10-phenanthroline) iron (II)